2021
DOI: 10.1007/s40615-021-01152-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Inpatient Mortality Disparities Among American Indian Adults in Mississippi’s Safety Net Hospital

Abstract: Background Long-standing health disparities experienced by American Indians (AIs) are associated with increased all-cause mortality rates and shortened life expectancies when compared to other races and ethnicities. Nationally, these disparities have persisted with the COVID-19 pandemic as AIs are more likely than all other races to be infected, hospitalized, or die from SARS-CoV-2. The Mississippi Band of Choctaw Indians, the only federally recognized American Indian tribe in the state, has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 5 publications
0
9
0
4
Order By: Relevance
“…A recent study in a single Mississippi hospital 21 found that even when controlling for the risk factors that the Centers for Disease Control and Prevention believed at the time put individuals at greatest risk of death from the novel coronavirus, American Indian and Alaska Native adults with COVID-19 had an in-hospital odds of death more than twice that of Black adults (odds ratio [OR], 0.23; P < .001) or White adults (OR, 0.24; P < .001). The authors therefore hypothesized that COVID-19 mortality rates would be significantly greater among American Indian and Alaska Native adults than those of any other race admitted to hospitals across the state and that higher COVID-19 in-hospital mortality rates among Indigenous patients would not be associated with greater comorbidity risk among American Indian and Alaska Native patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in a single Mississippi hospital 21 found that even when controlling for the risk factors that the Centers for Disease Control and Prevention believed at the time put individuals at greatest risk of death from the novel coronavirus, American Indian and Alaska Native adults with COVID-19 had an in-hospital odds of death more than twice that of Black adults (odds ratio [OR], 0.23; P < .001) or White adults (OR, 0.24; P < .001). The authors therefore hypothesized that COVID-19 mortality rates would be significantly greater among American Indian and Alaska Native adults than those of any other race admitted to hospitals across the state and that higher COVID-19 in-hospital mortality rates among Indigenous patients would not be associated with greater comorbidity risk among American Indian and Alaska Native patients.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Application to COVID-19 interrogations have also proven effective. [18][19][20] A recent study in a single Mississippi hospital 21 found that even when controlling for the risk factors that the Centers for Disease Control and Prevention believed at the time put individuals at greatest risk of death from the novel coronavirus, American Indian and Alaska Native adults with…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies were conducted in Michigan [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], six in New York [ 45 , 46 , 47 , 48 , 49 , 50 ], four in Atlanta [ 51 , 52 , 53 , 54 ], and four in California [ 55 , 56 , 57 , 58 ]. The remaining studies were divided as follows: one in three states (California, Oregon, and Washington) [ 59 ], one in Massachusetts [ 60 ], one in Tennessee [ 61 ], two in Wisconsin [ 62 , 63 ], one in Mississippi [ 64 ], one in Cleveland [ 65 ], one in Pennsylvania [ 66 ], two in Louisiana [ 67 , 68 ], one in the Midwest [ 69 ], one near the Mexico border [ 70 ], one in New Orleans [ 71 ], one in Georgia [ 72 ], one in Northeast Ohio and South Florida [ 73 ], one in Milwaukee and Southeast Wisconsin [ 74 ], one in Florida [ 75 ], one in Missouri [ 76 ], and one in Illinois [ 77 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the study design, the selected 59 studies can be categorized into studies that were retrospective in nature, cross-sectional in nature, association studies, case-control studies, and cohort studies. There were 45 studies that were retrospective in nature, including observational studies [ 19 , 20 , 22 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 43 , 44 , 46 , 47 , 49 , 51 , 52 , 53 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 68 , 70 , 71 , 72 , 76 ]. Additionally, there was one association study [ 37 ], seven cohort studies [ 21 , 24 , 25 , 28 , 45 , 54 , 73 ], five cross-sectional studies [ 23 , 55 , 63 , 74 , 77 ], and one case-control study [ 48 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation